Short-chain reactive probes as tools to unravel the Pseudomonas aeruginosa quorum sensing regulon. Issue 12 (18th February 2021) - Yashkin, Alex; Rayo, Josep; Grimm, Larson; Welch, Martin; Meijler, Michael M.
Abstract : Short-chain reactive probes can be used as tools to shed new light on virulence mechanisms in bacterial pathogens. Abstract : In recent years, the world has seen a troubling increase in antibiotic resistance among bacterial pathogens. In order to provide alternative strategies to combat bacterial infections, it is crucial deepen our understanding into the mechanisms that pathogens use to thrive in complex environments. Most bacteria use sophisticated chemical communication systems to sense their population density and coordinate gene expression in a collective manner, a process that is termed "quorum sensing" (QS). The human pathogen Pseudomonas aeruginosa uses several small molecules to regulate QS, and one of them is N -butyryl-l -homoserine lactone (C4 -HSL). Using an activity-based protein profiling (ABPP) strategy, we designed biomimetic probes with a photoreactive group and a 'click' tag as an analytical handle. Using these probes, we have identified previously uncharacterized proteins that are part of the P. aeruginosa QS network, and we uncovered an additional role for this natural autoinducer in the virulence regulon of P. aeruginosa, through its interaction with PhzB1/2 that results in inhibition of pyocyanin production.